Age-related tilt test responses in patients with suspected reflex syncope. Issue 7 (10th February 2021) - Rivasi, Giulia; Torabi, Parisa; Secco, Gianmarco; Ungar, Andrea; Sutton, Richard; Brignole, Michele; Fedorowski, Artur
Abstract: Aims: Tilt testing (TT) is recognized to be a valuable contribution to the diagnosis and the pathophysiology of vasovagal syncope (VVS). This study aimed to assess the influence of age on TT responses by examination of a large patient cohort. Methods and results: Retrospective data from three experienced European Syncope Units were merged to include 5236 patients investigated for suspected VVS by the Italian TT protocol. Tilt testing-positivity rates and haemodynamics were analysed across age-decade subgroups. Of 5236 investigated patients, 3129 (60%) had a positive TT. Cardioinhibitory responses accounted for 16.5% of positive tests and were more common in younger patients, decreasing from the age of 50–59 years. Vasodepressor (VD) responses accounted for 24.4% of positive tests and prevailed in older patients, starting from the age of 50–59. Mixed responses (59.1% of cases) declined slightly with increasing age. Overall, TT positivity showed a similar age-related trend ( P  = 0.0001) and was significantly related to baseline systolic blood pressure ( P  < 0.001). Tilt testing was positive during passive phase in 18% and during nitroglycerine (TNG)-potentiated phase in 82% of cases. Positivity rate of passive phase declined with age ( P  = 0.001), whereas positivity rate during TNG remained quite stable. The prevalence of cardioinhibitory and VD responses was similar during passive and TNG-potentiated TT, when age-adjusted. Conclusions: Age significantly impacts the haemodynamic pattern of TT responses, starting from the age of 50. Conversely, TT phase—passive or TNG-potentiated—does not significantly influence the type of response, when age-adjusted. Vagal hyperactivity dominates in younger patients, older patients show tendency to vasodepression.